Genotoxicity of cationic lipopeptide nanoparticles. (1st August 2020) - Zhanataev, Aliy K.; Anisina, Elena A.; Kulakova, Alla V.; Shilovskiy, Igor P.; Lisitsyn, Artem A.; Koloskova, Olesya O.; Khaitov, Musa R.; Durnev, Andrey D.
Highlights: Cationic lipopeptide nanoparticles caused DNA damage in liver, lung and kidney of mice. Genotoxicity was confirmed in vitro on human blood cells. No increase in chromosome aberrations in the bone marrow cells of mice. Abstract: The genotoxicity of cationic lipopeptide nanoparticles (cLPNPs) was evaluated in vivo and in vitro comet assay and the in vivo chromosome aberrations test. In vitro comet assay, human blood cells were exposed to cLPNPs at the concentration of 2.5, 5, 10, 20, 40 and 100 μg/mL. Significant DNA damage was observed after 1 h exposure, but no effects were detected after 3 h. In vivo, cLPNPs were administered in single or five daily injection doses at 8, 20 and 40 mg/kg of body weight by subcutaneous injection to male mice. The cLPNPs caused DNA damage in the liver, lung and kidney, but not in the spleen. The kidney was more prone to genotoxic effects that persisted from 24 h to 14d after a single injection of cLPNPs. No statistically significant increase in the percentage of cells with chromosomal aberrations above the vehicle control was observed in mice bone marrow after a single or repeated injection of cLPNPs. In summary, cLPNPs shown to be genotoxic both in vivo and in vitro . The results suggest the importance of the use of highly sensitive methods, such as the comet assay, in order to determine the full genotoxic potential of nanoparticles.